Evaluation of Serum Vitamin D3, PTH, Calcium and Iron Levels in Patients with H. pylori Infection: Evaluasi Kadar Vitamin D3, PTH, Kalsium dan Zat Besi Serum pada Pasien dengan Infeksi H. pylori - Obaid , Hussein Adnan; Salman , Noor Abd alkhudhur; Mohammad , Imad Jassim; Saadon , Hanan B.; Jabbar , Ali Hussein (Academia Open, 2024)
Helicobacter pylori (H. pylori) is a gram negative bacterium, the prevalence of which is associated with chronic gastric infection and nutritional abnormalities. The purpose of this study is to ascertain the relationship between H. pylori infection and serum vitamin D3, PTH, calcium and iron levels in adults. The cross-sectional study was carried out at Al-Nasiriyah teaching hospital 20 patient with H. pylori infection and 20 healthy individuals. Blood samples were also examined for the presence of vitamin D3, PTH, calcium and iron content. It is shown that H. pylori-positive patients had significantly decreased serum vitamin D3, calcium and iron concentration, and increased PTH level comparing with control group. These results provide preliminary evidence to indicate that H. pylori infection may cause disorders in vitamin D3, calcium, iron metabolism that maybe associated with the impaired nutrient utilization that has clinical significance such as osteoporosis and anemia. More studies should be done to discover the causes of these depots and their effects on individuals with H. pylori Highlights: H. pylori causes chronic gastric infections and nutritional issues. Infection reduces vitamin D3, calcium, iron; increases PTH levels. Linked to osteoporosis, anemia; further studies recommended. Keywords: H. pylori, Serum vitamin D3, Parathyroid hormone, Calcium levels, Iron